Novel method for the identification of circulating SARS-CoV-2 variants and clinical characteristics of patient infection with SARS-CoV-2 variants in Central China - Yuan, Youhua; Geng, Yiman; Rong, Tingjun; Wang, Baoya; Mao, Xiaohuan; Zhang, Xiaohuan; Zhang, Xiulei; Zhang, Yuan; Zheng, Peiming; Zhao, Jing; Guo, Fengxia (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionWe established a reliable and cost-effective method for identifying severe acute respiratory syndrome coronavirus 2 variants circulating in central China and analysed the clinical characteristics of patients with acute coronavirus disease 2019 who were infected with these variants.MethodsThe RNA of centrifuged and enriched samples was extracted and reverse transcribed into cDNA. cDNA was then analysed using a nested polymerase chain reaction amplification and Sanger sequencing method targeting specific mutations in the spike, ORF1a, and N genes. This was validated against next-generation sequencing, achieving 100% concordance.ResultsAmong 172 isolates, JN.1.18.2 was the most prevalent (52.9%, 91/172), followed by XDV.1 (25.0%, 43/172), JN.1.16 (20.9%, 36/172), and KP.2 (1.2%, 2/172), which was found in central China for the first time. Fever with cough (52.6%, 80/152) was the most common symptom and 59.9% (91/152) of patients had underlying conditions. JN.1.18.2-infected patients more frequently presented with double-lung computed tomography changes. A strong positive correlation was observed between the duration from hospital admission to the detection of SARS-CoV-2 variants and total hospitalisation duration.DiscussionThe new method provides a reliable tool for variant detection, highlighting milder clinical presentations in patients with active infections. Long-term monitoring of variants and patient characteristics is essential for effective prevention and treatment strategies.